The 3 December 1988 Pasadena, California earthquake : evidence for strike-slip motion on the Raymond fault - Sieh, Kerry (2013)
The Pasadena earthquake (ML = 4.9) occurred on 3 December 1988, at a depth of 16 km. The hypocenters of the earthquake and its aftershocks define a east-northeast striking, steeply northwest-dipping surface that projects up to the active surficial trace of the Raymond fault. One of the nodal planes of the focal mechanism of the earthquake parallels the Raymond fault with left-lateral strike-slip movement on that plane, and is consistent with geomorphic and paleoseismic evidence that the Raymond fault is dominantly a left-lateral strike-slip fault. The existence of a component of sinistral slip along the Raymond fault had been suspected prior to the earthquake, but the northward dip of the fault and the prominent scarp along the western portion of its trace had led most workers to conclude that slip along the fault was dominantly reverse.